2017
DOI: 10.1002/smtd.201700222
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose‐Nanofiber‐Enabled 3D Printing of a Carbon‐Nanotube Microfiber Network

Abstract: Highly conductive and mechanically strong microfibers are attractive in energy storage, thermal management, and wearable electronics. Here, a highly conductive and strong carbon nanotube/nanofibrillated cellulose (CNT–NFC) composite microfiber is developed via a fast and scalable 3D‐printing method. CNTs are successfully dispersed in an aqueous solution using 2,2,6,6‐tetramethylpiperidinyl‐1‐oxyl (TEMPO) oxidated NFCs, resulting in a mixture solution with an obvious shear‐thinning property. Both NFC and CNT fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 55 publications
2
125
0
Order By: Relevance
“…[1][2][3] Representative sustainable nanocellulose materials like cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs) have been used as primary constituent materials for additive manufacturing. [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…[1][2][3] Representative sustainable nanocellulose materials like cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs) have been used as primary constituent materials for additive manufacturing. [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…As a result, the embedded MWNTs were demonstrated to reduce the activation energy for the oxidative stabilization of cellulose nanofibers from about 230 to about 180 kJ/mol. In addition, Li et al reported that they developed highly conductive CNF-CNT microfibers using high-speed and scalable 3D printing techniques [110]. These microfibers can be normally dispersed in an aqueous solution using TEMPO-oxidized CNF, resulting in a mixed solution with obvious shear thinning properties.…”
Section: Fibersmentioning
confidence: 99%
“…[6,7] This is because the larger ionic radius of Na + is likely to result in serious structurald egradation as well as sluggish kinetic properties during the intercalation/deintercalation process. [27][28][29] Nanoscale particles can shorten ionic transfer pathways and increaset he available active material/electrolytei nterfaces.I mportantly,c arbonaceous materials can greatlyi ncreasee lectronic conductivity,t hus realizing a fast synergic transfer betweene lectrons and ions. Their robust 3D framework facilitates fast ionic transfer with little lattice expansion.…”
Section: Introductionmentioning
confidence: 99%